Algae-Derived Bioactive Compounds with Anti-Lung Cancer Potential - Imen Saadaoui (14159025) (2020)
Lung cancer is one of the major causes of death worldwide. Natural molecules with anti-lung cancer potential are of a great interest and considered as very promising alternative to substitute or enhance the efficiency of the conventional drugs. Recently, algae as source of high value-added compounds are considered as very promising source of these bioactive molecules. These are secondary metabolites that consist mainly of derivatives of peptides, carbohydrates, and lipids with various structures. Accordingly, various mechanisms by which different algae molecules demonstrate attenuation of tumor angiogenesis were stated and discussed. The mode of action of the algae bioactives is closely related to their nature and chemical structure. Furthermore, this literature review considers the synergistic effect between microalgae bioactives and conventional drugs and discuss the economic feasibility of producing microalgae bioactives at large scale to conclude with some future perspectives related to algae-based drug discovery. Other Information Published in: Marine Drugs License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/md18040197